A thermo-chemical and biotechnological approaches for bamboo waste recycling and conversion to value added product: Towards a zero-waste biorefinery and circular bioeconomy. (1st February 2023) - Ding, Zheli; Kumar Awasthi, Sanjeev; Kumar, Manish; Kumar, Vinay; Mikhailovich Dregulo, Andrei; Yadav, Vivek; Sindhu, Raveendran; Binod, Parameswaran; Sarsaiya, Surendra; Pandey, Ashok; Taherzadeh, Mohammad J.; Rathour, Rashmi; et al.
Graphical abstract: Highlights: Overview of recycling of bamboo biomass into high value added products. Thermo-chemical and biological conversion routes of bamboo lignin have discovered. Highlighted the strategies for pretreatment of bamboo biomass. Bio-valorization of bamboo biomass has been comprehensively explored. Abstract: Fast growth of bamboo species make them a suitable candidate for eco-restoration, while its lignocellulosic substrate could be used for production of high-value green products such as biofuels, chemicals, and biomaterials. Within these frameworks, this review comprehensively explored the thermochemical and biological conversion of bamboo biomass to value-added fuels and chemicals. Additionally, this review stretches an in-depth understanding of bamboo biomass lignin extraction technologies and bioengineered methodologies, as well as their biorefinery conversion strategies. Additionally, bamboo biomass often utilized in biorefineries are mostly constituted of cellulose, hemicellulose, and lignin, along with proteins, lipids, and a few micronutrients which are not utilized efficientely by current bioengineered techniques. The results indicates that the potential for producing high-value products from bamboo biomass has not been adequately explored. However, enormous potential is still available to make bamboo biorefinery technologies cost-effective, and environmentally sustainable, which are discussed in the current review comprehensively. Furthermore, processes such as pretreatment, enzymatic hydrolysis, and fermentation are essential to obtain final high-value bio-based products from bamboo biomass, therefore, this review critically designed to explore the current state of the art of these technologies. Overall, the current review establishes a zero-waste suastainable approachs for the reformation of bamboo biomass into chemicals, biofuels, and value-added products.